Sound and Fury Signifying Brexit - Gary Watt (Law Text Culture, 2020)
“Acoustic Jurisprudence” seeks to move our appreciation of the operation of sound in law beyond the merely metaphorical use of acoustic language to the audible quality of the soundscape itself. In this article, I connect the linguistic-metaphorical to the audible-sensory. My context is the ‘Brexit’ dispute as it has been played out in the UK Parliament, the UK Supreme Court, and elsewhere, especially as that dispute came to a crescendo on three occasions in the latter part of 2019. To describe those three occasions as moments of crescendo indicates that they can be appreciated as acoustic occasions, and specifically as acoustic occasions in a musical sense. The analogy of choral singing is the key musical analogy to which I will resort, not least in order to affirm the fundamentally important distinction between unison and harmony. To make peace after the discord of Brexit, we need to acknowledge that there can be no harmony when everybody sings the same tune. Harmony depends upon difference.